miR-339 Promotes Hypoxia-Induced Neuronal Apoptosis and Impairs Cell Viability by Targeting FGF9/CACNG2 and Mediating MAPK Pathway in Ischemic Stroke - Gao, Xiao-Zeng; Ma, Ru-Hua; Zhang, Zhao-Xia (Frontiers in Neurology, 2020)
Ischemic stroke (IS) is a common cerebrovascular disease characterized by insufficient blood blow to the brain and the second leading cause of death as well as disability worldwide. Recent literatures have indicated that abnormal expression of miR-339 is closely related with IS. In this study, we attempted to assess the biological function of miR-339 and its underlying mechanism in IS. By accessing to the GEO repository, the expression of miR-339, FGF9 and CACNG2 in middle cerebral artery occlusion (MCAO) and non-MCAO was evaluated. PC12 cells after oxygen-glucose deprivation/reoxygenation (OGD/R) treatment were prepared to mimic in vitro IS model. The levels of miR-339, FGF9, CACNG2 and MAPK-related markers were quantitatively measured by qRT-PCR and western blot. CCK-8 and flow cytometry analyses were performed to examine cell viability and apoptosis, respectively. IS-related potential pathways were identified using KEGG enrichment analysis and GO annotations. Bioinformatics analysis and dual-luciferase reporter assay were used to predict and verify the possible target of miR-339. Our results showed that miR-339 expression was significantly increased in MCAO and OGD/R-treated PC12 cells. Overexpression of miR-339 inhibited cell viability of PC12 cells suffered from OGD/R treatment. FGF9 and CACMG2 are direct targets of miR-339, and can reverse the aggressive effect of miR-339 on the proliferation and apoptosis of OGD/R-treated PC12 cells. Moreover, miR-339-mediated the activation of MAPK pathway was inhibited by FGF9/CACNG2 axis in PC12 cells treated by OGD/R stimulation. In summary, these findings suggested that miR-339 might act as a disruptive molecule to accelerate the IS progression via targeting FGF9/CACNG2 axis and mediating the MAPK pathway.